Mammary Gland Ultrasound Evaluation of Jersey Cattle Breed - Santos, Sthefany Kamile dos; Oliveira, Mariana Goncalves; Noriler, Elaine Pasqualin; Vrisman, Dayane Priscila [UNESP]; Bueno Borges, Luisa Pucci; Correia Santos, Victor Jose [UNESP]; Coutinho, Leandro Nassar; Maia Teixeira, Pedro Paulo (Univ Fed Rio Grande Do Sul, 2016)
Background: Ultrasound allows the udder evaluation of lactating cattle, through parameters such as the area of the cistern of the mammary gland and teat, and can reveal structures with different echogenicity, indicating injuries as mastitis, edema, hematoma, abscess, atrophy and fibrosis in the mammary gland parenchyma. The aim of this study was to observe the clinical, morphometric and sonographic assessment of the mammary gland of Jersey cows, evaluating the correlation of this exam and the production of milk. Materials, Methods & Results: Nine Jersey breed cows, aged 3 to 9 years, in a variable order of first to seventh lactation were evaluated. Animals were submitted to general and specific clinical examination of the mammary gland. For the evaluation, inspection and palpation of the gland cistern and teat cistern, measuring with tape measure the udder circumference and width and height of each mammary quarter was held, and length measurements of the four teats individually using a caliper. By palpation the mammary gland parenchyma was classified as nothing worthy of note and fibrosis. After this evaluation, the mammary glands were evaluated using ultrasound, analyzing biometrics and echotexture in order to detect and/or confirm possible changes identified in prior palpation. The diameter of the gland and teat cistern were measured, and the echogenicity of each region and each mammary quarter, checking the homogeneity of the parenchyma, evaluating the possible presence of nodules, scarring or acute injuries. The average milk production was 15.57 +/- 5.4 L. There was no correlation between milk production, measured biometric data of the mammary gland and clinical and ultrasonographic changes (P > 0.05). On palpation exam, a few number of animals had soft to normal consistency in mammary glands (2/9), the occurrence of fibrosis was observed, but could only be detected by ultrasonography (4/9). Discussion: Using the ultrasound examination is possible to access more accurately the morphology of the udder of lactating animals, examining and measuring the area of the cistern of the mammary gland and teat, the thickness of the wall and ceiling interface. Several studies correlate the morphology of these parameters with resistance to mastitis. The imaging aids to differentiate the teats according to animal age, milk production, lactation number, size, as well as a predisposition to mastitis. In healthy animals, the boundary between the gland cistern and teat cistern is marked by the presence of large anechoic structures. Changes in the teats of a gland with mastitis are mild inflammation, proliferation of tissues and mucosal lesions. No significant correlation between the morphology, physical examination and ultrasound changes of the mammary gland and milk production was observed. Possibly this was due to the limited number of experimental animals, and there is a wide variation in age and clinical profiles, as already observed in other studies that cows with high and wide rear udders tend to have higher milk production. In some cases ultrasound allows observe formation of gas, bruising, edema, abscess, atrophy, fibrosis, fistulae and intraluminal obstructions and parenchymal echogenicity changes during infection cases. In normal ultrasound examination, the parenchyma of the mammary gland must be homogeneous with high echogenicity and anechoic alveolus. Atresic and fibrosis are hyperechoic and lose the typical echogenicity of the udder. Thus, it is emphasized that ultrasound is a complementary method in the evaluation of the mammary gland, since it identifies not noticeable injuries on physical examination that may affect milk production.
Keywords: udder; mastitis; milk production; ultrasound